Peningkatan Keputusan Berinvestasi melalui Literasi Keuangan pada Generasi Z sebagai Upaya Persiapan Resesi 2023 - Sri Mulyono; Mohammad Sawir; Bambang Surahman; Erna Hendrawati; Nurhidayati Nurhidayati (ITB AAS INDONESIA, 2023)
The 2023 recession is currently a hot topic of discussion, especially in economic discussion forums. The 2023 recession requires efforts to prevent and reduce risks so that the impact is not too pronounced, especially for Generation Z from middle to lower economic families who are certainly very affected. This study aims to test and analyze the improvement of investment decisions through financial literacy in generation z as an effort to prepare for the 2023 recession. This research is a quantitative study by distributing questionnaires to respondents. The sample of this research is 100 generation Z whose sampling is done randomly. The questionnaire used has been tested for validity and reliability. The investment decision variable is measured by indicators of the level of expected return, the level of risk and the relationship between return and risk. While the financial literacy variable is measured by indicators of basic knowledge of financial management, credit management, savings and investment management. The data collected were analyzed by simple linear regression using SPSS version 23. The results of this study indicate that financial literacy has a positive and significant impact on the investment decisions of generation z, especially as an effort to prepare for the 2023 recession. These findings explain that if generation z wants to improve decisions In investing, Generation Z must also improve their financial literacy.